ATRA-like alkylation–peroxidation of alkenes with trichloromethyl derivatives by the combination of tBuOOH and NEt3. Issue 21 (3rd October 2018) - Chen, Cui; Tan, Hua; Liu, Bifu; Yue, Chaochao; Liu, Weibing
Abstract : This protocol provides a unique and innovative approach to the construction of α- tert -butylperoxy-β-dichloromethyl alkanes, employing CHCl3 as an alkylating reagent to provide a –CHCl2 group, and TBHP as an oxidant to provide an α- t BuOO group. Abstract : A method was developed for alkylation–peroxidation of alkenes using tert -butyl hydroperoxide (TBHP) and chloroform under metal-free conditions. This method is a unique and innovative approach to the construction of α- tert -butylperoxy-β-dichloromethyl alkanes, employing CHCl3 as an alkylating reagent to provide a –CHCl2 group, and TBHP as an oxidant to provide an α- t BuOO group. The reaction was successfully applied to carbon tetrachloride and 1, 1, 1-trichloroethane, and was regiospecific for terminal alkenes.